Ameliorating Lives in Cho Nam- Joo’s Novel Kim Jiyoung, Born 1982 (2016) - Made Miranti Khaerunisya; Desvalini Anwar (English Language and Literature, 2023)
This research is an analysis of the novel entitled Kim Jiyoung, Born 1982 (2016) by Cho Nam-Joo. This research reveals the amelioration of lives by South Korean women who live in patriarchal society. This research uses qualitative method and feminist theory to find out how South Korean women try their best to get a better life. The result of this research finds out that South Korean women who are portrayed in female characters of the novel Kim Jiyoung, Born 1982 (2016) by Cho Nam-Joo struggle a lot to make their live and other women’s lives around them to be better. The result also shows that they struggle against gender inequality in household, education, and workplace, which means in their whole life, women still get discrimination. The result shows that gender inequality happen because of the culture, society, and also the economy and education. Despite all of the difficulties and rejection they experience, the female characters in  women there still try to make a better life for themselves.